2022
DOI: 10.3390/drones6080200
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Adoption of Drones and Categorisation of Precision Elements among Hungarian Precision Farmers Using a Trans-Theoretical Model

Abstract: This article discusses the use of drones in Hungary and considers their future penetration, based on the responses to a nationally representative 2021 questionnaire among 200 large-scale farmers engaged in precision farming and in crop production. Both the applied trans-theoretical model (with ordinal logit regression model) and the questionnaire design are suitable for comparison with the results of a similar survey in Germany. In this study, similar results were found for farm size, age, main job and educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…The TAM has been criticized mainly for its simplicity and low explanatory power, but the model is still used extensively (Shachak et al, 2019;Weng Marc, 2018). The TTMA model used by Bai et al (2022) and Michels et al (2020) is based on the transtheoretical model of behavioral change (Prochaska & Velicer, 1997), consisting of multiple stages in the adoption process (i.e., no intention to use, intention to use, intention to use with a concrete plan, and already using). The transtheoretical model seems to be rather underexplored in agricultural research.…”
Section: Methodologies In Prior Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The TAM has been criticized mainly for its simplicity and low explanatory power, but the model is still used extensively (Shachak et al, 2019;Weng Marc, 2018). The TTMA model used by Bai et al (2022) and Michels et al (2020) is based on the transtheoretical model of behavioral change (Prochaska & Velicer, 1997), consisting of multiple stages in the adoption process (i.e., no intention to use, intention to use, intention to use with a concrete plan, and already using). The transtheoretical model seems to be rather underexplored in agricultural research.…”
Section: Methodologies In Prior Studiesmentioning
confidence: 99%
“…Regarding the use of UAVs, Bai et al (2022) showed that only approximately 25% of the surveyed farmers rejected using UAVs. Moreover, Chen et al (2020) identified that Chinese farmers had a slightly positive willingness to adopt on average.…”
Section: Study Descriptions and Farmers' Adoption Or Intention To Ado...mentioning
confidence: 99%
See 2 more Smart Citations
“…Through the use of Artificial Intelligence (AI) [8], Internet-of-Things (IoT) technologies [9,10], and big data analysis [11], the next wave of the agricultural revolution promises to reduce the aforementioned operational risks and promote the flow of information [12,13]. However, the introduction of such technologies in developing nations in Southeast Asia and elsewhere faces a number of particular difficulties, including the predominance of small and medium-sized farms, unusual farm conditions, inadequate capital support, and a lack of skilled management.…”
Section: Introductionmentioning
confidence: 99%